Desarrollo de habilidades sociales para la inclusión educativa de niños con Síndrome de Down - Pérez Corral, Zoila Maryorie (2023)
The research “ Development of social skills for educational inclusion of children with Down Syndrome”, it is allowed us to know the reality of the care given to students with SEN associated with a disability at the Liceo Naval Guayaquil Educational Unit, having in their classroom with a student with DS aroused interest in order to analyze to what extent the development of social skills favors then process of educational inclusion, another aspect to make highlight is the lack of knowledge of teacher to make significant curricular adaptation, and scarce application of innovative strategies for the reinforcement of social skills, which are essential within the teaching- learning process; when setting out as an objective: to analyze how the development of social skills contributes to educational inclusion, as a new model that allows timely care for children with DS within the classroom environment, the mixed approach allowed collecting information, applying techniques such as direct observation, the interview and the survey, which established, elaborate a guide of practical activities for the reinforcement of social skills, the same one that contributed with significant strategies; the one that allowed to improve the pedagogical ability, and the teaching competence, for a correct intervention with the children with DS, improving the interpersonal relationship and enhancing their social capacities in the different environments; with this work, we sought to sensitize all the actor of the educational community, involve parents, as primary collaborators in the learning processes, guaranteeing an inclusive quality education in our county.